Od realizmu do arealizmu (III). Deflacyjne rozwiązanie problematyki realizmu w filozofii powittgensteinowskiej - Oleksy, Mateusz (Filozofia Nauki, 2003)
The purpose of this article is to distinguish the position which I call „arealism” from both semantic realism and semantic anti-realism. Arealism is based on the deflationary critique of the logico-semantic debate on realism, i.e., on the argument which undermines the foundationist presuppositions of this debate. I attempt to draw carefully the distinction between arealist, deflationist approach to the problem of realism and the position of semantic anti-realism, which is usually framed in terms of the assertability-conditions semantics. Moreover, I argue that linguistic antirealism faces problems similar to those which haunted transcendental idealism. In the second part of the paper I demonstrate in a dialectical manner that arealism (1) is holistic in a particular Wittgensteinian sense, (2) does not support nor assume linguistic relativism, (3) should not be confused with meta-theoretical thesis of inexhaustibility of semantics, (4) involves a particular strategy of deflationary criticism, and (5) does not lead to semantic nihilism or eliminationism.